Dari Personalized Learning menuju Self-Regulated Learning: Model Konseptual Refleksi dan Internalisasi Nilai Berbasis Narasi Tokoh Alkitab - Lindawati; Khoe Yao Tung; Budi Wibawanta; Wiputra Cendana (Universitas Pelita Harapan, 2026)
This study addresses the challenge of developing self-regulated learning (SRL) among higher education students, particularly due to limited reflective capacity and weak value internalization in learning processes. While personalized learning enhances learner engagement, it does not automatically lead to SRL without deeper reflective and motivational mechanisms. This study aims to develop a conceptual model explaining the process from personalized learning to SRL through reflective thinking and value internalization based on Biblical narratives. Using a qualitative conceptual approach, this study employs an integrative literature review to synthesize theories on personalized learning, reflective thinking, value internalization, SRL, and narrative-based learning. The findings indicate that personalized learning initiates meaningful engagement, which triggers reflective thinking as a metacognitive process. The focus of this conceptual article is higher education students in a Christian educational context, particularly in relation to the formation of self-regulated learning through personalized learning, reflective thinking, value internalization, and Biblical narratives. The conceptual materials were processed through an integrative literature synthesis by identifying, categorizing, and relating key theoretical constructs from studies on personalized learning, reflective thinking, value internalization, SRL, and narrative-based learning. The synthesis is presented narratively and through a conceptual model that illustrates the processual relationship among the main constructs. Previous studies have examined these constructs separately but lack a processual explanation of their integration, particularly within narrative-based value formation. The novelty of this study lies in proposing an integrative conceptual model positioning reflective thinking as a metacognitive bridge and value internalization as a motivational mediator within a biblical narrative framework. The study concludes that SRL develops through a layered process integrating personalization, reflection, and value-based narrative learning.